Seleksi Saham Papan Utama Berbasis Rasio Keuangan dan Expected Shortfall Menggunakan Promethee Serta Evaluasi Sharpe Ratio - Di Asih I Maruddani; Rita Rahmawati (Jurnal Kajian Akuntansi, 2025)
The development of the Indonesian capital market requires stock selection methods that can comprehensively integrate financial statement information and market risk. Conventional approaches that rely on a single indicator are considered insufficient to capture the complexity of stock performance and risk. This study aims to select stocks in the Indonesian Main Board Index using the PROMETHEE method based on financial ratios and Expected Shortfall, and to evaluate risk–return efficiency using the Sharpe Ratio. This research adopts a quantitative approach using financial statement data for 2024 and daily stock price data from January 1 to December 31, 2025. The variables include liquidity, profitability, solvency, bankruptcy risk, stock return, and 95% Expected Shortfall. The results show that PROMETHEE is able to generate systematic stock rankings based on multi-criteria dominance, where stocks with the highest net flow exhibit better fundamental performance and lower extreme risk. However, further analysis reveals that stocks with the highest PROMETHEE rankings do not necessarily have the highest Sharpe Ratios, indicating differences in evaluation dimensions between the two methods. This study concludes that a two-stage approach PROMETHEE as an initial screening tool and the Sharpe Ratio as a subsequent evaluation provides more comprehensive insights for investment decision-making.